The Importance of Delegation of Authority, Budget Allocation and Leadership in Improving Performance - Jujun Juhana; Sadu Wasistiono; Irwan Tahir; Kusworo (GoAcademica Research & Publishing, 2020)
This study discusses the influence of delegation of authority, budget allocation and leadership to the performance of sub-districts in Garut Regency, West Java Province, Indonesia. This research uses a quantitative approach by collecting data in the form of questionnaires to respondents. The number of samples taken in this study was 286 respondents from a total population of 1003 people with a stratified random sampling technique. Data analysis techniques using SEM analysis. Based on the results of the study note that the delegation of authority, budget allocation, and leadership has a positive and significant effect on the performance of districts in Garut Regency, both partially and simultaneously.